Differential Effects of Warfarin on the Intracellular Processing of Vitamin K-dependent Proteins - Wu, Wei; Bancroft, John D; Suttie, J W (Thrombosis and Haemostasis, 1996)
The vitamin K-dependent carboxylation of specific glutamyl residues to γ-carboxyglutamyl residues occurs during the endoplasmic reticulum processing of a limited number of proteins. The fate of the under-γ-carboxylated proteins during protein processing was studied. When human hepatoma (HepG2) cells were grown in the presence of warfarin, under-γ-carboxylated prothrombin was secreted into the medium. In contrast, prothrombin secretion from a rat hepatoma (H-35) cell line was blocked by warfarin, and intracellular forms which were retained were degraded. When rat prothrombin (rFII) was stably transfected into warfarin treated HepG2 cells, endogenous human prothrombin (hFII) was secreted in an under-γ-carboxylated form, while rFII accumulated intracellularly. These data indicate that retention and degradation of under-γ-carboxylated prothrombin by human hepato-cytes is related to a structural difference in rFII and hFII. When rFII and hFII were transfected into a warfarin treated transformed human embryonic kidney cell line (293), both proteins were secreted in an under-γ-carboxylated form and intracellular retention was not observed. However, the secretion of rFII was greatly diminished. Cellular retention of under-γ-carboxylated forms is therefore tissue specific, but degradation is not.